Uji Efektivitas Ekstra Etanol Daun Salam (Syzygium Polyanthum (Wight) Walp) Terhadap Profil Histologi Pankreas Tikus Putih Jantan (Rattus Norvegicus) Diabetes Melitus - Gerhart Frengki Hardian Harefa; Erida Novriani; Asyrun Alkhairi Lubis (Jurnal Sains Farmasi Dan Kesehatan, 2025)
ABSTRACT Diabetes mellitus is a chronic metabolic disorder characterized by hyperglycemia due to impaired insulin secretion or function, which can damage organs, including the pancreas. Natural treatment alternatives are needded because conventional drugs cause side effects. Bay leaf, also known as Syzygium polyanthum (Wight) Walp, contains bioactive compounds like flavonoids, tannins, and saponins that have potential to fight diabetes and protect pancreatic tissue. The aim of this study is to determine the effect of bay leaf extract on the histology of the pancreas in diabetic rats and to identify the optimal dose to reduce pancreatic tissue damage. This study used 25 male Rattus norvegicus rats and was conducted experimentally with a pretest-posttest control group design. The rats were divided into 6 groups: normal control, negative control (NaCMC), positive control (metformin), and three treatment groups given bay leaf extract at doses of 200 mg/kgBW, 300 mg/kgBW, and 400 mg/kgBW. For 15 days, the extract was administered orally, and blood glucose was measured; therefore, bay leaf extract can be used as an alternative to improve pancreatic damage caused by diabetes.